The Conference NOISE CONTROL 95. - ENGEL, Z. (Archives of Acoustics, 1996)
The lOth International Conference on Protection Against Noise NOISE CONTROL 95 was held in Warsaw on June, 20-22nd, 1995. The conference was arranged by the Acoustic Committee of the Polish Academy of Sciences, the Polish Acoustic Society and the Central Institute for Labour Protection by co-operation with the Department of Mechanics and Vibroacoustics of the Academy of Mining and Metallurgy and the Department of Acoustics of the Building Research Institute in Warsaw.